Konstantinos Kavafis, Obra poética completa, edición bilingüe de Alfonso Silván Rodríguez, Madrid, Ediciones La Palma, 1991 ISBN 84-87417-12-4 (Minerva, 2019)
Review: Konstantinos Kavafis, Obra poética completa, edición bilingüe de Alfonso Silván Rodríguez, Madrid, Ediciones La Palma, 1991 ISBN 84-87417-12-4